Local governments' changing power in South Africa's energy system: reshaping the regulatory space for renewable energy, from the bottom up - Hermanus, Lauren (Graduate School of Development Policy and Practice, 2017)
In 1994, South Africa's post-apartheid government inherited a highly-centralised energy sector, in which all aspects including planning, procurement, generation, distribution, pricing, and management were determined through top-down institutional arrangements and investments, centred around Eskom. In 2016, however, following rounds of energy sector reform, and the successful implementation of the Renewable Energy Independent Power Producers Procurement Programme (REIPPPP), this centralised configuration of power showed signs of disruption. Municipalities began to ambitiously redefine their role by building on opportunities related to renewable energy, resulting in an emergent challenge to centralised energy policy and planning. This dissertation sought to explore how this contestation took shape and to explain how seemingly ad hoc actions have created new possibilities, as well as new regulatory frameworks, by municipalities for municipalities. To achieve this, an analysis of the evolution of decentralised renewable energy generation in South Africa between 2008, when it first began, and 2016, was undertaken, applying the method of process tracing to two case studies. In order to contextualise these bottom-up processes within the national political economy of energy, process tracing was also applied in a high-level analysis of countervailing movements that consolidate centralised energy planning and procurement during the same period, with a particular focus on national plans to undertake massive investments in nuclear energy. It was found that municipalities' bottom-up actions have positioned them to drive renewable energy in such a way that seriously challenges the historical configuration of power that has determined South Africa's energy future up to now.